Seasonal variation in feeding habits and diet selection by wild boars in a semi-arid environment of Argentina - Cuevas, Maria Fernanda (2013)
The wild boar, Sus scrofa, was first introduced for hunting purposes in Argentina in 1906 and presently occupies a wide range of habitats. Understanding the food habits of invasive species is important for predicting the effects of animal food consumption on the environment and on human activities, such as farming. The wild boar is an omnivorous, opportunistic species whose diet is determined by the relative abundance of different types of foods. In general, the wild boar´s diet has been widely studied in the world, both as a native and invasive species, but little is known regarding food resource selection in the Monte Desert biome. Our study assessed the seasonal variation in the diet of wild boars, as well as the nutritional quality of consumed items. Further, we determined the diet selection of this species. Diet analyses were based on faecal samples collected over two seasons (wet and dry) during one year. Herbs were the most frequently consumed food item, with wild boars showing a selection for them in both seasons. The wild boar uses food resources according to seasonal availability (larger trophic niche breadth under higher plant diversity, as in the wet season). In turn, within each season, it selects items of high forage quality and high carbohydrate contents. In conclusion, this foraging strategy enables wild boar to maximize energy budget through food selection in order to survive in a semi-arid environment such as the Monte Desert.